2022
DOI: 10.1292/jvms.21-0648
|View full text |Cite
|
Sign up to set email alerts
|

Maximum volume of nasal administration using a mucosal atomization device without aspiration in Japanese White rabbits

Abstract: Recently, a mucosal atomization device (MAD) has been applied in veterinary medicine. In the present study, the maximum volume of nasal atomization without aspiration using MAD was examined in eight healthy female Japanese White (JW) rabbits. Each rabbit had their head and neck examined by computed tomography before and after nasal atomization with four different doses (0.15, 0.3, 0.45, and 0.6 ml per nostril) of diluted contrast medium (1:2 mixture of iohexol and saline). This was done under general anesthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In JW rabbits, 0.3 mL is the maximum non-aspiration single dose of INA using the MAD [37]; however, the presence or absence of aspiration in multiple 0.3 mL INAs has not been investigated. Although a total of 0.6 mL of 1 mg/mL medetomidine formulation was administered into both nasal cavities by twice atomization in the MED1.2 treatment developing severe hypoxemia, the rabbits successfully recovered from the hypoxemia by oxygen supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In JW rabbits, 0.3 mL is the maximum non-aspiration single dose of INA using the MAD [37]; however, the presence or absence of aspiration in multiple 0.3 mL INAs has not been investigated. Although a total of 0.6 mL of 1 mg/mL medetomidine formulation was administered into both nasal cavities by twice atomization in the MED1.2 treatment developing severe hypoxemia, the rabbits successfully recovered from the hypoxemia by oxygen supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxemia is developed by five potential causes such as alveolar hypoventilation, ventilation-perfusion ratio mismatch, diffusion impairment, right-to-left shunt, and low partial pressure of inspired oxygen [ 28 , 32 ]. In JW rabbits, 0.3 mL is the maximum non-aspiration single dose of INA using the MAD [ 37 ]; however, the presence or absence of aspiration in multiple 0.3 mL INAs has not been investigated. Although a total of 0.6 mL of 1 mg/mL medetomidine formulation was administered into both nasal cavities by twice atomization in the MED1.2 treatment developing severe hypoxemia, the rabbits successfully recovered from the hypoxemia by oxygen supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…have reported that 0.3mL was the optimum volume for intranasal delivery of drugs via the MAD without tracheal aspiration in rabbits. However, with a delivery volume of 0.45 or 0.6mL, the MAD was able to deliver particles to the rabbit trachea ( 81 ). Although these findings demonstrate a proof-of-principle that the MAD syringe can potentially deliver drugs/vaccines to the lower respiratory tract, further investigations are required to evaluate the optimal delivery volume of TB vaccines, particularly in humans.…”
Section: Potential Tb Vaccine Delivery Devicesmentioning
confidence: 99%
“…In veterinary medicine, the MAD has been used for the administration of anticonvulsant and sedative drugs in dogs [ 29 , 30 , 31 , 32 , 33 ]. Recent studies report the use of the MAD for the administration of a single sedative or anesthetic drug, such as medetomidine and alfaxalone, and other molecules, in rabbits [ 34 , 35 , 36 , 37 ]; furthermore, the maximum administrable volume using the MAD without aspiration into the trachea was evaluated in Japanese White rabbits [ 38 ].…”
Section: Introductionmentioning
confidence: 99%